Management of palatine tori: Penatalaksanaan torus palatinus - Kusumaputra, Juliani; Salim, Supardi; Kartika, Dewi (Makassar Dental Journal PDGI Makassar, 2025)
One of the obstacles experienced by dentists when making dentures is the protrusion on the maxillary bone known as torus pala-tinus. A 70-year-old woman came to RSGM-Yarsi accompanied by her child, complaining of a lump on the palate but not painful and the patient planned to make a denture. The general condition was good, extra oral examination was good, intra oral examina-tion showed a bone protrusion with a wide base, smooth surface and slightly convex on the palate durum size was bigger than 6 mm. This article discusses palatinus torectomy in an elderly patient prior to denture placement. It is concluded that palatine torectomy is one of the appropriate preprosthetic surgical treatments to reduce maxillary bone protrusion for denture fabrication.